Orphanage trafficking in international law - Van Doore, Kathryn (Cambridge University Press, 2022)
The process of orphanage trafficking in developing states -- The enabling environment for orphanage trafficking -- The demand of orphanage tourism -- Situating orphanage trafficking in international law -- Responding to orphanage trafficking.